Auxin-Induced Epinasty of Tobacco Leaf Tissues (A Nonethylene-Mediated Response). - Keller, C. P. (1997)
Interveinal strips (10 x 1.5 mm) excised from growing tobacco (Nicotiana tabacum L. cv Xanthi) leaves curled >300[deg] when incubated for 20 h in 5 to 500 [mu]M [alpha]-naphthalene acetic acid or 50 to 500 [mu]M indole-3-acetic acid. Epinasty was not induced without auxin or by the auxin analog [beta]-naphthalene acetic acid, and less substantial epinasty was induced in midrib and vein segments. Auxin treatment increased the length of both surfaces of strips. Curvature resulted from greater growth on the adaxial side. Epinastic sensitivity of strips to auxin appeared first in the distal third of young leaves (blade 4.5-6.0 cm). In older leaves (8-10 and 12-14 cm), the interveinal tissues throughout were sensitive, whereas in leaves 16- to 18-cm long, sensitivity was reduced in the distal two-thirds. Amino-oxyacetic acid (AOA), an ethylene biosynthesis inhibitor, partially inhibited epinasty at 100 [mu]M. However, a poor correlation between inhibition of ethylene biosynthesis by AOA and its inhibition of curvature and the inability of ethylene to produce epinasty or to reverse the effects of AOA suggests that auxin-induced epinasty is not caused by auxin-induced ethylene production.